How do wild birds adjust to captivity? Impacts on stress physiology and behavior. - Fischer, Clare. (2017)
Abstract: When wild animals are brought into captivity, they experience many stimuli that may be interpreted as potentially dangerous and activate the stress response, a set of hormonal pathways that are activated to maintain homeostasis in the face of harmful stimuli. If stressors are repeated or ongoing, the stress response may become dysregulated and lead to the suite of symptoms known as "chronic stress." In this dissertation, I reviewed the current literature to determine whether chronic stress decreases with time after capture, indicating adjustment to captivity. While some chronic stress symptoms frequently decrease over time (i.e. weight loss, leukocyte redistribution), other symptoms can linger for months or years in some species (i.e. elevated glucocorticoids, reproductive dysfunction). I conducted several experiments on the chronic stress of captivity in newly-captured wild house sparrows (Passer domesticus). I monitored glucocorticoid levels, adrenomedullary variables, and weight in house sparrows over the first 6 weeks of captivity. The birds had decreased mass up to day 35, elevated baseline glucocorticoids at day 7 that then declined, and elevated heart rate until day 20, indicating that the animals suffered chronic stress that only decreased after several weeks. To determine whether chronic captivity stress could be reduced pharmacologically, I tested the effects of 4 drugs over the first 7 days of captivity. The anxiolytic diazepam and the α-adrenergic receptor antagonist phentolamine had no effect on chronic stress. The β-adrenergic receptor propranolol prevented the increase in baseline glucocorticoids. Mitotane (which causes chemical adrenalectomy) resulted in decreased heart rate after 1 week, even when it did not cause the expected reduction of glucocorticoids. The hormones of stress can influence behavior. Neophobia, or the fear of novel objects, is an ecologically relevant, easily quantified behavior. While characterizing neophobia in captive wild birds, I documented a seasonal effect on food motivation in house sparrows. Finally, I analyzed the connection between the adrenomedullary response and neophobia in another passerine, the European starling (Sturnus vulgaris). I found no relationship between heart rate and behavior. Therefore, not every aspect of captivity (i.e. novelty) may contribute to the overstimulation of the stress response leading to chronic stress symptoms.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Biology.; Advisor: L. Michael Romero.; Committee: J. Michael Reed, Philip Starks, and Brian Walker.; Keywords: Endocrinology, Physiology, and Biology.